Muamalah Fiqh Analysis On Hybrid Contract Model And Its Application To Islamic Financial Institutions - Vivi Aulia Safitri; Koni Piranda; Riyandi Fatur Nugraha (Penerbit Jurnal Indonesia, 2023)
This paper is intended to analyze philosophically about the existence of a hybrid contract (english) or al-‘Uqûd al-Murakkabah (Arabic) or multiakad (Indonesia). Search focused on the opinion of scholars of hadith and fiqh (muamalah), as well as its application in Islamic Financial Institutions. This is important, because, in the form of a single contract is not able to respond to contemporary financial transactions which always move and are affected by the financial industry both nationally, regionally and internationally. By using qualitative and literature method, the study concluded that, firstly, fiqh muamalah contemporary view of the hadith related to contract hybrid models lead to the editorial about the ban of bai’ataini fi bai’atin (two sale and purchase in the sale), ban of shafqataini fi shafqatin (two agreements in the deal) and the prohibition of bay’ and the salaf (sale and purchase agreement and ordering of goods), secondly, the construction of contract hybrid models in Islamic banks is addressed to the construction of al- ‘Uqûd al-Mutaqâbilah (dependent or conditional contract), which implemented on Guarantee Bank (BG), and al-‘Uqûd al-Mujtami'ah (same type contract), which implemented on the Housing Financing.